Evaluasi dan Perbaikan Usability Aplikasi Bangbeli dengan menggunakan Metode Usability Testing dan Use Questionnaire - Khoirul Abdul Jamil; Komang Candra Brata; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Bangbeli is a mobile application engaged in fintech. Bangbeli's main goal is to help UMKM traders who want to compete in credit transactions, game vouchers, service payments, etc. Bangbeli entered the Google market for the first time on January 26, 2020. Bangbeli has been downloaded more than 10,000 times and has more than 1000 reviews with a rating of 4.6. Bangbeli has quite interesting and good reviews. After conducting an interview with the Bangbeli developer, there was an urgency from the Bangbeli business team to create an account tier system to boost user interest in making transactions more often. In the Oxford dictionary it is described as a row or level in a structure, which is placed one above and shrinks in size. Therefore, the need for usability testing to measure the level of feasibility and explore the problems of the new feature. Meanwhile, usability testing is a process that involves people as test participants who evaluate the extent to which a product meets the usability criteria. This study author used usability testing and the USE Questionnaire. According to ISO international standards, usability includes three aspects, namely efficiency, effectiveness and satisfaction. he Usefulness and Ease of Use parameters in the USE questionnaire have correlations in these three aspects. Two tests will be performed to get a good score, initial testing and final testing. To get analysis values and evaluating recommendations requires Initial testing. The final score will be obtained from the final test conducted after the evaluation process. The usability result before the improvement recommendation was 75.59% with a good value and the usability value after the display improvement recommendation was 75.36% with an excellent value.